Hypertonic saline and mannitol in patients with traumatic brain injury: A systematic and meta-analysis. Issue 35 (28th August 2020) - Shi, Jiamin; Tan, Linhua; Ye, Jing; Hu, Lei
Abstract: Background: To compare the effects of 3% hypertonic saline solution and 20% mannitol solution on intracranial hypertension. Methods: WAN-FANGDATA, CNKI, and CQVIP databases were searched, and relevant literatures of randomized controlled trials comparing 3% hypertonic saline solution with mannitol in reducing intracranial hypertension from 2010 to October 2019 were collected. Meta-analysis was performed using RevMan software. Results: : As a result, 10 articles that met the inclusion criteria were finally included. A total of 544 patients were enrolled in the study, 270 in the hypertonic saline group and 274 in the mannitol group. There was no significant difference in the decrease of intracranial pressure and the onset time of drug between the 2 groups after intervention (all P > .05). There was a statistically significant difference between the hypertonic saline group and the mannitol group in terms of duration of effect in reducing intracranial pressure (95% confidence interval: 0.64–1.05, Z  = 8.09, P  < .00001) and cerebral perfusion pressure after intervention (95% confidence interval: 0.15–0.92, Z  = 2.72, P  = .007). Conclusion: Both 3% hypertonic saline and mannitol can effectively reduce intracranial pressure, but 3% hypertonic saline has a more sustained effect on intracranial pressure and can effectively increase cerebral perfusion pressure.